Different levels of endemicity of Lihué Calel National park, La Pampa, Argentina (Semiárida, 2022)
The concept of endemism, its controversies and possible origins are discussed. Examples of different degrees of endemicity of plant species present in the Lihué Calel National Park are presented and the importance of their study and preservation is raised.
Keywords: endemicity; Lihué Calel National Park